2020
DOI: 10.1017/s0007114519003398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing of food intake on eating patterns, diet quality and weight gain during pregnancy

Abstract: Studies have suggested that meal timing plays a role in nutritional health, but this subject has not been sufficiently studied in pregnant women. We analysed the effect that timing of food intake has on eating patterns, diet quality and weight gain in a prospective cohort study with 100 pregnant women. Data were collected once per trimester: 4th–12th, 20th–26th and 30th–37th weeks. Food intake was evaluated using three 24-h dietary recalls, which were used to assess eating patterns and diet quality. Distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Time-related eating patterns, including the number of meals, eating duration, the time of the first and last meal, 12 h nightly fasting, and the caloric midpoint, were calculated by the research team from the 3-day food recall—two days of work and one day of rest. This methodology has been widely applied in chrononutritional studies [ 33 , 40 , 41 ]. First, the number of meals was established by the number of caloric events ≥50 kcal/day with time intervals of ≥15 min between meals [ 42 ] reported in the dietary record.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-related eating patterns, including the number of meals, eating duration, the time of the first and last meal, 12 h nightly fasting, and the caloric midpoint, were calculated by the research team from the 3-day food recall—two days of work and one day of rest. This methodology has been widely applied in chrononutritional studies [ 33 , 40 , 41 ]. First, the number of meals was established by the number of caloric events ≥50 kcal/day with time intervals of ≥15 min between meals [ 42 ] reported in the dietary record.…”
Section: Methodsmentioning
confidence: 99%
“…The study of dietary patterns related to the time of day has brought a new approach to nutritional studies, especially due to the demonstrated relationship between such patterns and metabolic diseases [ 28 , 29 , 30 ], as well as the overall quantity and quality of food eaten [ 31 , 32 , 33 ], including food with high carbohydrate, fat, and sugar content. These variables include the time of meals, daily distribution of energy and nutrients, the 24 h food window (eating duration), and caloric midpoint, which is the time of day when 50% of the calories consumed in the day are reached [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been growing interest in the timing of eating beyond traditional dietary approaches focusing on foods and nutrients. Longer duration of food intake for each day, irregular eating, and eating at the wrong time are associated with more energy intake and poor diet quality [21][22][23][24]. Previous studies have shown that late eating is associated with reduced efficacy of weight loss intervention compared…”
Section: Introductionmentioning
confidence: 99%
“…Erratic eating patterns have been found to adversely influence obesity, diabetes, metabolic syndrome, and cardiovascular diseases [ 21 , 25 , 28 , 29 ]. However, that evidence was obtained from carefully controlled feeding studies with specific populations such as pregnant women or obese adults [ 21 , 22 , 25 , 27 ]. There is little evidence available on characteristics related to eating time, BP control, and cardiometabolic health among adults with hypertension in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados mostraram que gestantes com tendência a matutinidade apresentaram melhor qualidade da dieta identificada pelo Índice de Qualidade da Dieta Revisado (IQD-R) para população brasileira, com escores mais elevados para a pontuação total e para o componente frutas totais.Os autores também afirmaram que outros componentes do IQD-R -como "carnes, ovos e leguminosas", "vegetais totais", "vegetais verdes-escuros e alaranjados e leguminosas" -provavelmente não foram associados ao cronotipo porque são grupos alimentares que incluem tipos de alimentos geralmente consumidos durante grandes refeições -como almoço e jantar -(que não são negligenciadas independente do cronotipo) pela maioria dos brasileiros(DE OLIVEIRA SANTOS et al 2015). Além disso, também encontramos que durante a gestação mulheres com uma maior alimentação noturna eram mais propensas a ter um cronotipo noturno(GONTIJO et al 2020). excessivo do que gestantes com menor ingestão energética noturna, o que supostamente poderia ser justificado pela variabilidade cronotípica entre o grupo.Esses resultados devem encorajar estudos futuros que possam estudar um possível efeito deletério da alimentação noturna por gestantes com tendência à vespertinidade sobre o ganho de peso durante a gestação.…”
unclassified